Urban Agglomeration and Firm Innovation : Evidence from Developing Asia - Chen, Liming; Hasan, Rana; Jiang, Yi (World Bank, Washington, DC, 2021)
This paper examines the relationship between urban agglomeration and firm innovation using a recently developed dataset that consistently measures city boundaries across Asia together with geo-referenced firm-level data. It finds that the spatial distribution of innovation by firms is highly concentrated within countries. Further, firms in larger cities have substantially higher propensities to introduce product and process innovations and undertake R&D activities, a result that holds for subgroups of countries and even when the largest cities are excluded from the analysis. Finally, the presence of high quality universities and highly ranked engineering departments in cities is positively associated with firm innovation, lending support to the idea that the accumulation of human capital locally is a key channel through which urban agglomeration affects innovation.